The Orientation of β2GPI on the Plate is Important for the Binding of Anti-β2GPI Autoantibodies by ELISA - Iverson, G.Michael; Matsuura, Eiji; Victoria, Edward J.; Cockerill, Keith A.; Linnik, Matthew D. (Journal of autoimmunity, 2002)
(β2-glycoprotein I (β2GPI) is a plasma protein that plays an important role in the antigenic specificity of antiphospholipid autoantibodies (aPL). These antibodies are associated with an increased risk for thrombosis and recurrent foetal loss in humans. Crystallographic analysis of β2GPI showed that its five complement control protein (CCP) or ‘sushi’ domains are arranged in an elongated, fish-hook shape; yet the domain-specific location of epitopes recognized by these autoantibodies has remained the subject of considerable controversy. Investigators have used different forms of recombinant β2GPI and different ELISA methods to obtain conflicting results. One group mapped autoimmune epitopes to domain I using deletion mutants of β2GPI in a competitive inhibition ELISA on NUNC Maxisorp™ microplates. Another group mapped epitopes to domain IV using β2GPI with mutations in domain IV in a direct binding ELISA on polyoxygenated microplates. In an effort to resolve these discrepancies, a collaboration between the groups compared wildtype β2GPI with domain IV mutants in both types of ELISA. Autoantibodies bound very poorly to domain IV mutants coated on polyoxygenated plates, yet they bound very well to the same mutants coated on NUNC Maxisorp™ plates. The amount of protein adsorbed on to both types of plates was similar. In the competitive inhibition ELISA, no difference could be detected between wildtype β2GPI and domain IV mutants. These results strongly suggest that the orientation of β2GPI on the microplate, and not necessarily the lateral density, plays the predominant role in the binding of autoantibodies.